Precarious democracies, political negotiation and selective predation - Cendales, Andrés; James Mora, Jhon (Estudios Económicos de El Colegio de México, 2015)
This paper demonstrates that a precarious democracy is harmful to the poor rather than benefiting them as long as the governing party, being a highly informal organization, includes a cartel of political patrons and business people. The mayor is unable to govern freely due to controls or vetoes exercised by those collective actors to which he/she belongs. Not having been elected democratically, the objective of these groups is to co-opt the state at the subnational level by violating civil rights and liberties on election days and committing crimes against the public administration during the term of government.